Defected ZnWO4-decorated WO3 nanorod arrays for efficient photoelectrochemical water splitting. Issue 10 (13th February 2019) - Cui, Ya; Pan, Lun; Chen, Ying; Afzal, Nisha; Ullah, Sana; Liu, Danyang; Wang, Li; Zhang, Xiangwen; Zou, Ji-Jun
Abstract : A strategy based on a solvothermal method was developed to construct defected ZnWO4 -decorated WO3 photoanodes for efficient photoelectrochemical water splitting. Abstract : The utilization of solar energy in photoelectrochemical water splitting is a popular approach to store solar energy and minimize the dependence on fossil fuels. Herein, defected ZnWO4 -decorated WO3 nanorod arrays with type II heterojunction structures were synthesized via a two-step solvothermal method. By controlling the amount of Zn precursor, WO3 nanorods were decorated in situ with tunable amounts of ZnWO4 nanoparticles. Characterization confirmed the presence of abundant W 5+ species in the defected ZnWO4 -decorated WO3 samples, leading to enhanced light absorption and charge-separation efficiency. Therefore, the decorated WO3 nanorod arrays show much higher photoelectrochemical (PEC) activity than pure WO3 nanorod arrays. Specifically, the sample with optimal ZnWO4 decoration and surface defects exhibits a current density of 1.87 mA cm −2 in water splitting at 1.23 V vs. RHE under 1 sun irradiation (almost 2.36 times higher than that of pure WO3 ), a high incident photon-to-current efficiency of nearly 40% at 350 nm, and a relatively high photostability. However, the decoration of WO3 with too much ZnWO4 blocks the light absorption of WO3, inhibiting the PEC performance, even when many defects are present. This work provides a promising approach to rationally construct defected heterojunctions as highly active PEC anodes for practical applications.